Revision of Isoglaridacris (Cestoda: Caryophyllidea), parasites of suckers (Catostomidae) in North America: molecular phylogeny and description of four new species - Dalibor Uhrovič; Camila Pantoja; Olena Kudlai; Tomáš Scholz (Scientific Reports)
Abstract The caryophyllidean tapeworms (Cestoda) of the genus Isoglaridacris Mackiewicz, 1965 are revised on the basis of the study of type specimens and newly collected material from suckers (Cypriniformes: Catostomidae) in North America. Molecular data reveal the presence of 14 lineages, each representing a separate species. An overview of all nominal species is provided, with updated information on their hosts, distribution and phylogenetic relationships. Isoglaridacris multivitellaria Amin, 1976 is excluded from Isoglaridacris, but its generic affiliation remains unclear, and it is considered incertae sedis. Homeomorpha mackiewiczi Dutton et Barger, 2014 from Minytrema melanops is transferred to Isoglaridacris as I. mackiewiczi (Dutton et Barger, 2014) new combination. Based on molecular and morphological data, four new species are described: Isoglaricris mattisi n. sp. from Moxostoma collapsum in South Carolina, USA, I. mcallisteri n. sp. from Erimyzon claviformis in Arkansas and Oklahoma, USA, I. mexicanus n. sp. from Moxostoma cf. austrinum in Chihuahua, Mexico, and I. floriani n. sp. from M. macrolepidotum in South Carolina. A key to the identification of all 16 valid species is provided. Isoglaridacris species exhibit strict host specificity, with most species parasitising only a single host species (strict specialists), while a few species occur in more than one species within the same host genus (congeneric specialists). The distribution range of Isoglaridacris species includes southern Canada, the United States and northwestern (nearctic) Mexico.